Dosimetric evaluation of gold nanoparticle aided intraoperative radiotherapy with the Intrabeam system using Monte Carlo simulations - Moradi, F.; Abdul Sani, S.F.; Khandaker, Mayeen Uddin *; Sulieman, A.; Bradley, D.A. * (Elsevier, 2021)
Radiosensitization using high atomic number nanoparticles (NPs) has been shown to be an effective method to enhance radiotherapy efficiency. The pathways by which NPs cause sensitization, are generally categorized as physical, chemical and biological effects. Specifically in the case of keV photon radiotherapy where the contribution of physical effects in radiosensitization mechanism is considerable, Monte Carlo (MC) simulations have been an efficient tool to predict the radioenhancement level and to calculate dose enhancement factor (DEF). To-date, several analytical, simulational and experimental studies have reported the radiosensitization effect of gold nanoparticles (GNPs) in various brachytherapy situations. In this work we report for the first time, the DEFs achievable in intraoperative radiotherapy through use of the Intrabeam system and its spherical applicators with addition of GNPs. The MCNPX Monte Carlo code was used for radiation transport and dose calculations. The results of macroscopic and microscopic analysis show that for the Intrabeam system and a homogeneous distribution of 50 nm diameter GNPs, respective DEFs of up to some 1.5, 2, 2.5 and 3 in the tumour bed can be achieved with 5, 10, 15 and 20 mg/g concentrations. Due to rapid change in electron spectra, DEFs greater than 1 mm separation from the applicator surface decrease with distance, offering an additional advantage.